Efeito do decanoato de nandrolona associado ao exercício de carga na expressão do fator de crescimento de endotélio vascular (VEGF) no músculo sóleo de ratos - Paschoal, Milena de Moura (2008)
Androgenic-anabolic steroids have been used both for performance improvement and aesthetic reasons. It is well know that high doses of AAS can raise serious adverse effects such as skeletal muscle injuries including increase in the rate of muscle strains/ruptures. The aim of this study was to investigate VEGF mRNA expression in the rat soleus muscle after jumping training associated with androgenic-anabolic steroids (AAS) administration. Wistar rats were grouped into: sedentary (S); trained without AAS (T); nandrolone decanoate (ND)-treated sedentary (AAS); and trained with AAS (AAST). The trained groups have carried out jumps in water at 32°C.: 4 series of 10 jumps each, with a 30-second interval among series, for 7 weeks, with 50- 80% overload of the animal corporal mass. The AAS (Decadurabolin® - 5mg/kg) was injected via subcutaneous in animal back twice a week. Real-time PCR analyses have shown that training significantly increased VEGF mRNA expression in comparison with the S, AAS groups. When training exercise was associated with nandrolone decanoate, the VEGF mRNA expression was inhibit compared with T group. The inhibited expression of VEGF by AAS administration could cause diminished angiogenesis in skeletal muscle. These results suggest that the AAS may be strongly prejudicial to muscle remodeling and performance.